Study of Desiccation Crack Behavior of Fly Ash - Bentonite (FAB) Composite in Landfill Liner System - Eflita Yohana; Syafrudin Syafrudin; Mochamad Arief Budihardjo; Bimastyaji Surya Ramadan; Ayudya Izzati Dyah Lantasi; Fadel Iqbal Muhammad; Natasya Ghinna Humaira (Universitas Diponegoro, 2022)
The addition of bentonite to fly ash can lower the permeability coefficient of the composite landfill liner. Also, the montmorillonite bentonite can bind quite a lot of water molecules during the hydration process. In this study, the effect of mixture, water content, and salinity on the desiccation cracking phenomenon in the bentonite - fly ash mixture as a landfill liner system was investigated by conducting tests such as desiccation test, water content test, and standard proctor and permeability test. The variation in bentonite levels: 0%, 15%, 20%,25% and 25% + 1 N NH4Cl solution. The result shows that the appropriate mixture is fly ash + 15% bentonite with permeability of 4,065 x 10-7. The mixture complies with local regulations where the permeability coefficient of the bottom layer of the landfill should be less than 10–6 cm/s and have a low cracking value (CIF). Furthermore, the addition of saline solution to the composite can rise the value of the optimum moisture content. However, saline conditions can decrease the value of CIF drastically